Innovate to Educate: Use of mobile devices in the teaching and learning of English - Nuez, Graciela; Sánchez Suárez, José A. (Historia y Comunicación Social, 2014)
The use of mobile devices to teach and learn English involves a deep exploration of our practice and teaching design. This paper reveals through the paradigm of cognitive science core concepts that have sustained the Spanish education, it suggests the use of the mobile devices as tools to develop innovation and finally it examines various materials available online to apply in educational environments.